The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41467-018-02820-0
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical dysrhythmia detected by machine learning

Abstract: Thalamocortical dysrhythmia (TCD) is a model proposed to explain divergent neurological disorders. It is characterized by a common oscillatory pattern in which resting-state alpha activity is replaced by cross-frequency coupling of low- and high-frequency oscillations. We undertook a data-driven approach using support vector machine learning for analyzing resting-state electroencephalography oscillatory patterns in patients with Parkinson’s disease, neuropathic pain, tinnitus, and depression. We show a spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
153
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 182 publications
(172 citation statements)
references
References 72 publications
10
153
3
Order By: Relevance
“…The original TCD study suggested that the theta burst mode shown by thalamic neurons, replacing alpha and gamma frequencies, is because of activation of low‐threshold calcium spike bursts that are induced by long‐lasting hyperpolarization generated on altered projections from the globus pallidus or the pedunculopontine nuclei (PPN) to the thalamoreticular nuclei (TRN). Contrary to earlier studies that have proposed TCD as the mechanism for PD motor symptoms, more recent evidence indicates that PD‐related theta‐pre‐alpha EEG activity only correlates with ongoing cognitive decline and not with motor symptoms . We therefore suggest that the TCD theory should be repositioned from being the conceptual framework of PD motor symptoms to a central role in driving DMN decoupling and ensuing disconnections from contextual and consensual reality, that is, hallucinations, SFDs, delusions, and fluctuating cognition.…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingcontrasting
confidence: 70%
See 4 more Smart Citations
“…The original TCD study suggested that the theta burst mode shown by thalamic neurons, replacing alpha and gamma frequencies, is because of activation of low‐threshold calcium spike bursts that are induced by long‐lasting hyperpolarization generated on altered projections from the globus pallidus or the pedunculopontine nuclei (PPN) to the thalamoreticular nuclei (TRN). Contrary to earlier studies that have proposed TCD as the mechanism for PD motor symptoms, more recent evidence indicates that PD‐related theta‐pre‐alpha EEG activity only correlates with ongoing cognitive decline and not with motor symptoms . We therefore suggest that the TCD theory should be repositioned from being the conceptual framework of PD motor symptoms to a central role in driving DMN decoupling and ensuing disconnections from contextual and consensual reality, that is, hallucinations, SFDs, delusions, and fluctuating cognition.…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingcontrasting
confidence: 70%
“…DMN decoupling should be linked with the (now) uncontroversial evidence of EEG abnormalities in PDD and DLB, consisting of the progressive appearance of theta rhythms . These rhythms are the core features of the thalamocortical dysrhythmia (TCD) theory, which postulates that in several disorders including PD, thalamocortical neurons enter into a state of theta burst mode that drives cortical EEG theta and dysfunctional cortical activity . These theta rhythms, now used as a diagnostic biomarker, are the hallmark of thalamocortical dysfunction, as EEG rhythmic activity needs a thalamic pacer, only arrhythmic activities depend on focal cortical alterations .…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingmentioning
confidence: 99%
See 3 more Smart Citations